Consideraciones sobre los alumnos que abandonan el sistema escolar y las repercusiones sobre la formación de los profesores. - Macías Gómez, Escolástica (Revista Complutense de Educación, 2006)
Each sholar year a high number of pupils of "secondary obligatory education" (spanish high school) abandon the scholar system without enough knowledges to base the adquisition or the development of suitabilities for the professional exercise. In this pages man pretends ton analize some considerations about what happen in classroom between teacher and pupils, from interactive process and trying to show some modifications that could be introducted in the formations of teachers to improve the docent practice, so that them favor learning process of the pupils in a so decisive stage as is the "secondary obligatory education ".